Evaluación de tres dosis de hormona de crecimiento (GH) en conejos en la fase de finalización en Pillaro - Tungurahua - Bejarano Rivera, Cristina Isabel (2012)
The investigation was make in The Company Village, that is located in President´s Urbina town in Píllaro, Tungurahua state, for about 30 days; the objective of the investigation was testing the three levels of grow up hormone (0,1; 0,2; 0,3 ml) in rabbits in the final stage to identify the changeable growing as. Besides to analyzed productions costs with the treatments of studies and identifies the most effective treatment for the investigation. The chapter 1 is stables of one bibliography which includes general regards of anatomy and physiology about rabbits digestive chemistry, how then arguments of bovine somatotropin; the chapter 2 is describing the location at the investigation, investigations design, variable compilation of production and economy analysis; in chapter 3 we have the experimental design analysis, and the discussion of the results, conclusions and the recommendations….